Plano de carreira, cargos e salários: ferramenta favorável à valorização dos recursos humanos em saúde pública - Costa, Adriana Cristina Oliveira [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2010)
Human recourses on Brazilian Health System (SUS) are important social points because on this form the State can guarantee the health like a right of Brazilian population, based on National Constitution Dictates. The Plan of Offices, Careers and Salaries (PCCS) is an administrative tool that should be elaborated to attendance objectives of organization. It maintain the satisfaction level of workers, with a politic of Human Recourses that allows its development and so, can get higher productivity, efficiency and objectivity of services rendered at community. The aim of this study is to contextualize the PCCS like an instrument of People Management to guide and incentive one of forms to turn no precarious the work force of Public System Dental Professionals in SUS. For them, it was realized a literature review, and official documents of Health Ministry were consulted, like governmental decrees, laws, health conference written report. It was possible to verify that, although there is legal basement on the use of PCCS-SUS by Brazilian cities like a tool to attract and maintain dental surgeon developing his profession on SUS, is often the absence of valorization of this professional, and this situation no allows his exclusive dedication at health public services. Precarious work in Dentistry is still observed on many regions of Brazil.

Os recursos humanos no Sistema Único de Saúde (SUS) são sujeitos sociais importantes para que o Estado, apoiado nos ditames da Constituição Brasileira, garanta a saúde como direito à população brasileira. O Plano de Carreira, Cargos e Salários (PCCS) é uma ferramenta administrativa que deve ser elaborado para atender aos objetivos da organização mantendo o nível de satisfação dos servidores, com uma política de Recursos Humanos que permita seu desenvolvimento para, então, ter produtividade, eficiência e objetividade dos serviços prestados à comunidade. O propósito deste artigo é de contextualizar o PCCS como instrumento de Gestão de Pessoas, para nortear e incentivar uma das formas de desprecarização da força de trabalho de profissionais de Odontologia do SUS. Foi realizada uma revisão da literatura e consultados documentos oficiais do Ministério da Saúde, como portarias, leis, relatórios de conferências de saúde. Verificou-se que, embora exista apoio legal para que os municípios utilizem o PCCS-SUS como ferramenta para atrair e manter o dentista a desenvolver sua profissão no SUS, ainda é constante a falta de valorização deste profissional, o que impede sua dedicação exclusiva aos serviços públicos de saúde, haja vista que o trabalho precário em Odontologia é observado em várias regiões do Brasil.
Plan of careers, offices and salaries: tools favorable at valorization of recourses on public health
Keywords: Human recourses; Health management; Dental care; Salaries; Health services; Recursos humanos; Gestão em saúde; Odontologia; Salários; Serviços de saúde